Prediksi Hasil Ujian Kompetensi Mahasiswa Program Profesi Dokter (UKMPPD) dengan Pendekatan ANFIS - Fajri Marindra Siregar; Gunadi Widi Nurcahyo; Sarjon Defit (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2018)
The main objective of this study was to predict the outcome of student's competency exam of the medical profession (UKMPPD) using Adaptive Neuro-Fuzzy Inference System (ANFIS). Data obtained from the Faculty of Medicine Universitas Riau’s student database in 2015 which amounted to 170 data. Input variables were membership status, length of study, and grade point average. Furthermore, the data were analyzed using MATLAB software by setting the number of membership function 2 2 2 and Gbell membership function. The results showed that the method is able to predict the outcome of UKMPPD with Mean Average Percentage Error (MAPE) 0.07%, minimum 0.00%, and maximum 0.44%.